Analisis Pemasaran Susu Segar di Kabupaten Klaten - Handayani, Sugiharti Mulya; Nurlaila, Ivana (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2011)
This study aimed to determine the marketing channels of fresh milk in Klaten , costs, benefits, marketing margin and efficiency. The basic method used was the descriptive analysis and purposive sampling with the Kayumas Village, Jatinom was selected as a place for the research. In total, 30 dairy farmers were taken as samples by random sampling method. Meanwhile, traders samples taken by snowball sampling consisted of two traders, 3 and 1 meddle retailers. The data used were primary and secondary data taken in April 2010 with interview techniques, recording and observation. Data was analyzed using cost margin analysis.The results of this study showed that there were two patterns of fresh milk marketing channels. Channels I: dairy farmers → TPS → KUD → IPS, home industry, retailers and consumers. Channel II: dairy farmers → collectors → traders from outside of Jatinom. In the first line the total marketing cost was Rp. 263.76, total marketing profit was Rp. 143.26 and marketing margins was Rp. 328.26 per liter. For marketing channel II total marketing cost was Rp. 52.93, total marketing profit was Rp. 60.07 and marketing margins was Rp. 81.50 per liter. Both of the channels were efficient with the farmer's share of 89.06% for channels I and 97.24% for channel II.